39.8k views
4 votes
Simplify the expression. 12x^-6 y^10 times 3x^7 y

User Ondrs
by
5.4k points

1 Answer

3 votes

We need to simplify the expression:


12x^(-6)y^(10) * (3x^(7)y)

Now, we know that we can resolve the exponents of the variables with the like terms only and we can multiply the coefficients independently:

Now,


12x^(-6)y^(10) * 3x^(7)y=(12 * 3)* (x^(-6)* x^(7))* (y^(10)* y)

On simplifying the above expression we get:


36* x^((-6+7))* y^((10+1))


=36 * x^(1)* y^(11)


=36 * x * y^(11)


=36xy^(11)

So the simplified form of the expression
12x^(-6)y^(10) * 3x^(7)y=36xy^(11).

User Anton Rybalko
by
5.9k points